Une Française dans la forêt canadienne : sur l’écriture de Marie Le Franc - Patrycja Tomczak (Studia Romanica Posnaniensia)
Due to historical and cultural factors, French-Canadian and Quebec literature has traditionally been sparse in its engagement with nature writing. This void was addressed in the 1920s and 1930s by writers who emigrated from France to Canada, notably Marie Le Franc. An exploration of the depictions of time, space, and subjectivity in her works, compared to the novels of Hémon, Constantin-Weyer, and Bugnet, unveils the distinctly vegetal quality of Le Franc’s prose and her profound connection to the forest.